1998
DOI: 10.3758/bf03206173
|View full text |Cite
|
Sign up to set email alerts
|

“Transient structures”: The effects of practice and distractor grouping on within-dimension conjunction searches

Abstract: It has been stated that whereas between-dimension (color x orientation) conjunctions can be searched in a "parallel" fashion, within-dimension (color x color) conjunctions are necessarily searched in a "serial self-terminating" fashion (Wolfe et al., 1990). We explored the effects of practice (within 1-h experimental session) and distractor grouping on within-dimension conjunction search tasks. In Experiments 1 and 3, the stimuli were rectangles formed by two adjacent squares; in Experiment 2, the stimuli were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 70 publications
4
35
0
Order By: Relevance
“…Participants had to detect the presence or absence of a target object that was defined by a specific colour/ colour combination (e.g., red above green). The small display set size reduces the possibility that target selection was primarily based on the colour-based perceptual grouping of distractors, as previously found for colour/colour conjunction search with dense displays (Carrasco et al, 1998;Linnell & Hymphreys, 2001). On no-competition trials, one targetmatching object (either the target or a distractor object that matched the top or bottom colour of the target, e.g., red above blue) was presented among three nonmatching, nontarget objects.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Participants had to detect the presence or absence of a target object that was defined by a specific colour/ colour combination (e.g., red above green). The small display set size reduces the possibility that target selection was primarily based on the colour-based perceptual grouping of distractors, as previously found for colour/colour conjunction search with dense displays (Carrasco et al, 1998;Linnell & Hymphreys, 2001). On no-competition trials, one targetmatching object (either the target or a distractor object that matched the top or bottom colour of the target, e.g., red above blue) was presented among three nonmatching, nontarget objects.…”
Section: Introductionmentioning
confidence: 77%
“…This specific assumption is based on experiments demonstrating that search for targets defined by a conjunction of two colours or two orientations is much less efficient than search for colour/ shape conjunctions (Wolfe et al, 1990; see also Wing & Allport, 1972). However, other studies have suggested that colour/colour conjunction search can be relatively efficient (Carrasco, Ponte, Rechea, & Sampedro, 1998) and that pairs of colour/colour conjunction targets can be processed in parallel (Linnell & Hymphreys, 2001). For example , Carrasco et al (1998) showed that when all distractor objects share the same nontarget colour, practice led to highly efficient colour/colour conjunction search, presumably due to the colour-based perceptual grouping of distractors and the subsequent rapid rejection of these grouped non-target objects (see Linnell & Hymphreys, 2001;2002, for further evidence of within-dimension grouping effects in this type of search task).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The guided-search model can account for this finding by assuming that participants conduct a separate evaluation of the number of red items and blue items in a display and then search through the smaller subset of distractors. This flexible change in search behaviors can be seen as another exception (see also the efficient within-dimension conjunction search with practice by Carrasco et al, 1998 and with part-whole configuration by Wolfe et al, 1994) to the general nature of inefficient within-dimension conjunction searches ).…”
Section: Distractor-ratio Effect 28mentioning
confidence: 99%
“…The combination of these activations would guide attention towards the red horizontal item. However, in a within-dimension search task, activation emerges from one dimension only, and the features can be searched only in a serial fashion because it is not possible for one feature module to handle two simultaneous topdown requests for activation ; but see Carrasco, Ponte, Rechea, & Sampedro, 1998 for evidence of efficient within-dimension searches). Given the argument by Wolfe and his colleagues Wolfe et al, 1994;Wolfe, 1994Wolfe, , 1996 that within-dimension conjunction searches are processed in a qualitatively different fashion from cross-dimension conjunction searches, Experiment 2 was designed to examine whether the distractor-ratio effect is also observed in within-dimension conjunction search tasks by employing a color × color within-dimension conjunction search task.…”
Section: Current Studymentioning
confidence: 99%